Influence of a River Corridor on the Variation of Climate Elements: The Case of Neuquén City (Argentina) - Lopez, Micaela; Gentili, Jorge Osvaldo (Revista Geográfica de América Central., 2024)
This paper aimed to compare the behavior of climatic elements and extreme thermal events between two landscape units of the city of Neuquén, Argentina, for the period 2013-2020. The study involved daily data of minimum temperature (Tmin), maximum temperature (Tmax), and relative humidity (RH) obtained from the meteorological stations "Neuquén Aero" (NA) and "Paseo de la Costa" (PC), referring to the valley (peri-urban area) and the fluvial corridor (riparian environment) respectively. The influence of the riverbank on the daily Tmin and Tmax during Heat Waves (HW) and Cold Waves (CW) in the valley was analyzed using the methodology of the National Meteorological Service. The mean Tmax (Tmin), at annual, seasonal, and monthly resolutions, were lower (higher) in PC. The mean RH values were higher in NA. During the HW, a regulatory effect was exhibited regarding the number of days that the threshold values were exceeded consecutively in the fluvial littoral.